Changes in functional disorders of the wrist and hand as a marker of the effectiveness of a physical therapy programme for patients with rheumatoid arthritis - A. Nogas; I. Grygus (Kazimierz Wielki University, 2022)
Annotation. Rheumatoid arthritis is regarded worldwide as one of the most common pathologies and is one of the most significant medical, social and economic problems of modern society. According to modern concepts, along with drug therapy, physical therapy plays an important role in the system of health recovery for patients with rheumatoid arthritis. The purpose of the paper is to determine the effectiveness of a physical therapy programme based on the results of wrist and hand function in patients with rheumatoid arthritis. Materials and methods. A total of 188 patients with rheumatoid arthritis were examined, including 156 women (83%) and 32 men (17%). All patients were randomly assigned to the control (n=92) and intervention (n=96) groups. Patients in the control group underwent physical therapy in accordance with the recommendations of the regulatory document of the Ministry of Health of Ukraine. Patients in the main group were engaged in a developed physical therapy programme, taking into account factors affecting the level of functional impairment and quality of life. Rehabilitation measures were developed with a personalised approach to each patient, for a long-term period of 6 months. The main section of the DASH (Disability of the Arm, Shoulder and Hand Outcome Measure) questionnaire was used to assess functional impairment of the wrist and hand in patients with rheumatoid arthritis. Results. Both standard treatment and physical therapy after 3 months contributed to the recovery and improvement of the DASH questionnaire scores in both groups, but the changes in the intervention group were more pronounced than in the control group, where the scores were lower. Thus, the number of people in the main group who had a good result increased - 27.1%, in the control group only 17.5% of patients had a good result; 52.1% of patients in the main group had a satisfactory result, 50.0% in the control group; 20.8% of patients in the main group and 32.5% of patients in the control group still had an unsatisfactory result. The analysis of the results after 6 months of physical therapy showed a significant improvement in the examined patients of the main group: a good result was noted by 49.0% of patients, which is 25.0% more than in the control group - 24.0% of patients. A satisfactory result was found in 39.6% of patients in the main group and in 57.6% of patients in the control group, which is 18.0% more than in the control group. Conclusion. The above results of the DASH questionnaire in the main group, which are significantly better than those of the control group, indicate the justification of a new marker of the effectiveness of the proposed physical therapy programme for patients in the main group.